Era New Normal Terhadap Tingkat Kepuasan Pengunjung Pada Masa Pandemi Covid-19 di Pariwisata Pantai Pasir Putih Bira Bulukumba - Indah Wahyuni; Andi Cudai Nur; Muh Rizal S; Andi Caesar To Taddampali (xxxx-xxxx, 2023)
This study aims to determine the new normal era on the level of visitor satisfaction in tourism on the white sand beach of Bira Bulukumba. This research uses quantitative methods. Data collection techniques used were observation and questionnaires. The population in this study was 64,191. The sampling method used is Isaac and Michael's table with a simple random sampling technique, as many as 346 people. The data obtained from the research results were processed using the SPSS 25 application which consists of validity and reliability tests, descriptive data analysis techniques and inferential analysis.          The results showed that the new normal was in the good category, the level of satisfaction was in the very good category. The results of inferential analysis show that there is a significant effect between the new normal on the level of visitor satisfaction at the White Sand Beach Tourism of Bira Bulukumba.